Transformations in the European Gas Supply Network Due to the Russia–Ukraine Conflict - Theodore Tsekeris (Energies)
The objective of this paper is to demonstrate the structural characteristics of the European gas supply system and changes in its network structure and the interaction and clustering among its nodes defined as countries, following the outbreak of the Russia–Ukraine conflict. The methodology relies on social network analysis, which employs mathematics of the graph theory to examine the state and dynamics of the given network structure. The impacts identified involve the reduced reliance of the system on Russian gas, a considerable reduction in the strength centrality of Russia and Germany, and a higher dispersion of gas flows, largely due to the increased import of LNG flows. After the conflict outbreak, countries such as Italy, Austria, the Slovak Republic, and Hungary retained their high influential position, in terms of the PageRank centrality, while the Balkan countries, together with the Middle East gas suppliers (Turkey and Iran), formed a common group with Russia. The estimated changes stress the challenges posed to the EU countries to enhance connectivity infrastructure investments and explore alternative ways of gas supply to support the objectives of strategic autonomy, while promoting resilience and the path toward a carbon-free transition.